2009
DOI: 10.1016/j.jasms.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discrimination of archaeal tetraether lipid cores by liquid chromatography-tandem mass spectrometry

Abstract: Atmospheric pressure chemical ionization liquid chromatography-tandem mass spectrometry (APCI LC-MS/MS) of tetraether lipid cores of archaeal origin reveals distinct dissociation pathways for three classes of core lipid extracted from Methanobacter thermautotrophicus. Within these classes, two isobaric tetraether lipids, one a scarcely reported lipid constituent of M. thermautotrophicus and the other an artefact formed during extraction from cultured cells, were identified and distinguished via their MS 2 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 26 publications
10
82
0
Order By: Relevance
“…The novel 2G-methylated GDGT (2G-Me-GDGT; IPL-14) and 2G-dimethylated GDGT (2G-diMe-GDGT; IPL-15) were identified by exact masses after Q-TOF-MS and MS/MS fragmentation patterns (Table 2; Figure 3), which were consistent with the Me-GDGT core lipids reported by Knappy et al (2009) and Knappy (2010). These methylated core lipids (i.e., 1316.3Da and 1330.4 Da, respectively) were generated via removal of the 2G headgroups after mild acid hydrolysis (Meador et al, unpublished data) and co-eluted with GDGT (1302.2 Da) during normal phase chromatography, further confirming that the additional methyl group was located in the biphytanyl chain and not in the glycerol moiety (Zhu et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…The novel 2G-methylated GDGT (2G-Me-GDGT; IPL-14) and 2G-dimethylated GDGT (2G-diMe-GDGT; IPL-15) were identified by exact masses after Q-TOF-MS and MS/MS fragmentation patterns (Table 2; Figure 3), which were consistent with the Me-GDGT core lipids reported by Knappy et al (2009) and Knappy (2010). These methylated core lipids (i.e., 1316.3Da and 1330.4 Da, respectively) were generated via removal of the 2G headgroups after mild acid hydrolysis (Meador et al, unpublished data) and co-eluted with GDGT (1302.2 Da) during normal phase chromatography, further confirming that the additional methyl group was located in the biphytanyl chain and not in the glycerol moiety (Zhu et al, 2014).…”
Section: Resultssupporting
confidence: 84%
“…Zhu et al, 2014a; 15 ± 3.1%), archaeol (AR; 10 ± 1.5%), isoprenoidal glycerol dialkanol diethers (GDDs; cf. Knappy et al, 2009;Zhu et al, 2014a], was not detected in the CL fraction or as a hydrolysis product of the IPL fraction in any sample. Zhu et al, 2014a; 1.0 ± 0.5%; Table 1).…”
Section: Quantification Of Archaeal Cls and Iplsmentioning
confidence: 81%
“…To this end, Buckles and colleagues (2013) suggested that relative enrichments of an archaeal tetraether lipid, the taxonomically widely distributed glycerol dibiphytanyl glycerol tetraether without cyclopentane rings [i.e. Fortunately, recent advances in the analysis of intact polar lipids (IPLs; Sturt et al, 2004;Wörmer et al, 2013;Zhu et al, 2013) and core lipids (CLs; Knappy et al, 2009;Liu et al, 2012a,b;Becker et al, 2013;Zhu et al, 2014a,b) have already expanded the catalogue of microbial biomarkers and enhanced the ability to find biomarkers associated with the presence of MCG, which could lead to the identification of specific lipid biomarkers. However, the utility of GDGT(0) as universal biomarker for MCG is severely limited due to the widespread occurrence of this lipid in many archaeal phyla (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with this genus OPUs 23,24,25,26 and 27) and Har. marismortui (47 isolates in OPU 28) species could also be identified.…”
Section: Affiliation Of the Otus Corresponding To The Archaeal Fractionmentioning
confidence: 94%